2015
DOI: 10.1016/j.gecco.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Ecological changes induced by full-sun cocoa farming in Côte d’Ivoire

Abstract: h i g h l i g h t s• Ecological impacts of sun-grown cocoa farming in Côte d'Ivoire were assessed. • Biodiversity and soil properties were measured along a chronosequence. • Plant species richness and diversity markedly decreased from forest to cocoa stands. • Earthworm abundance and species richness increased due the appearance of species adapted to degraded lands. • Full-sun cocoa farming significantly deteriorated soil quality. a b s t r a c tFull-sun cocoa farming is currently the most widespread cocoa cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 61 publications
8
53
0
2
Order By: Relevance
“…For instance, Dawoe et al (2014) reported that, in humid lowland Ghana, soil properties and quality parameters of a Ferric Lixisol improved under cocoa plantations that have been operating for 15-30 years and were better than that of a YCP with a 3-year production age. Similar results were obtained by Tondoh et al (2015), who reported that, in Côte d'Ivoire, there was a steady degradation of soil quality over time in full-sun cocoa stands planted on Ferralsols for 10 years, but the degradation value was less pronounced in 20-year-old plantations.…”
Section: Mds Normalization Transformation and Integration Into Csdisupporting
confidence: 88%
See 4 more Smart Citations
“…For instance, Dawoe et al (2014) reported that, in humid lowland Ghana, soil properties and quality parameters of a Ferric Lixisol improved under cocoa plantations that have been operating for 15-30 years and were better than that of a YCP with a 3-year production age. Similar results were obtained by Tondoh et al (2015), who reported that, in Côte d'Ivoire, there was a steady degradation of soil quality over time in full-sun cocoa stands planted on Ferralsols for 10 years, but the degradation value was less pronounced in 20-year-old plantations.…”
Section: Mds Normalization Transformation and Integration Into Csdisupporting
confidence: 88%
“…Comparing our results with those of Dawoe et al (2014) and Tondoh et al (2015) highlights the effects of poor and unsustainable land management practices on soil degradation in peasant cocoa agroecosystems in West Africa. Traditionally, cocoa plots are cultivated with food crops in the first 3 to 5 years of development until the canopies have formed.…”
Section: Classification Into Degradation Classessupporting
confidence: 57%
See 3 more Smart Citations